The Selfie as profile photo on Facebook: an identity, sociability and entertainment resource - Molina Parral, Angélica (2023)
The purpose of this paper is to analyze the meanings attributed by a small group of young provincial female university students to the production and dissemination of the selfie as profile pictures on Facebook and to the social interaction that is woven around it. The empirical evidence supporting the work derives from interviews with nine women between the ages of 17 and 21, who are residents of the towns of Cuautla and Cuernavaca (located in the eastern Mexican state of Morelos), are undergraduate students and are users of Facebook, as well as observations made on this network. The main findings point to the fact that the selfie as a profile picture is a resource for identity, sociability and entertainment. The young women in the study produce and disseminate selfies as part of their leisure activities, without previous reflection or preparation. Neither does it seem that their selfies have been made so that the others who see them, reflect upon them.